Educational Training and Training of Adult Women in the pilot center of Pueblo Nuevo (Revista Electrónica REDINE, 2024)
The purpose of this article is to analyze the importance of entrepreneurship and empowerment in the training of adult women, based on the training process carried out at the Pueblo Nuevo Enterpreneurship School of Barquisimeto, Lara state, Venezuela. Given the importance that the training of women has today within government educational policies oriented towards adult education, in this school, a constant training process is carried out, where adult women learn through entrepreneurship, to have a different vision of life, perspectives that allow you to empower yourself and create businesses with the knowledge acquired, becoming successful and productive activities for the participants in this process; Hence. They become women with other perspectives, who take advantage of opportunities and put into practice the knowledge they acquire from this type of training. That is why, in this essay, emphasis is placed on the importance of this type of training and training for women, based on entrepreneurship and empowerment, providing them with new life alternatives on a personal, social, educational and economic level, among others, through educational processes as fundamental axes of their training.
Keywords: Entrepreneurship; empowerment; education of Venezuelan adult women